Depression and somatic diseases – how are they linked? - Wiklińska, Agata; Szydło, Jakub; Tkaczyk, Ignacy; Rybacka-Tkaczyk, Katarzyna (Quality in Sport, 2025)
Introduction and aim of study: Depressive disorder is one of the most common diseases involving mental health. It is known as a stress-dependent disease. It triggers a number of mechanisms, which are supposed to ensure homeostasis to the body. However, under prolonged stress, they become harmful to the organism, causing a number of somatic diseases. The aim of this paper was to discuss the cause-effect relationship between depression and somatic comorbidities. Materials and methods: Databases such as PubMed and Google Scholar were searched to review the scientific literature on the association between depression and somatic comorbidities. The following keywords were used for the search: depression, somatic diseases, inflammation, HPA axis and lifestyle. Results: A review of the literature showed an increased prevalence of cardiovascular diseases, obesity, diabetes, infections and cancer among patients with depressive disorder. The most important processes underlying these correlations were: hyperactivity of the HPA axis, hyperactivity of the sympathetic nervous system and inflammation. Conclusion: In patients suffering from depression, attention should be paid to the increased incidence of somatic diseases. Both oncological and internal medicine vigilance should be increased in the treatment.